The new paradigm in thermodynamic formulation of electrolytic systems - A review - Anna M Michałowska-Kaczmarczyk; Tadeusz Michałowski (Archive of Biomedical Science and Engineering - Peertechz Publications, 2019)
The general property of electrolytic systems in aqueous media is presented. The linear combination f12 = 2∙f(O) - f(H) of elemental balances: f1 = f(H) for Y1 = H and f2 = f(O) for Y2 = O, is put in context with charge balance (f0 = ChB) and other elemental and/or core balances fk = f(Yk) (k=3,...,K) related to the system in question It is stated that f12 is (a) linearly independent on f0,f3,...,fK for a redox system, or is (b) linearly dependent on f0,f3,...,fK when related to a non-redox system. The balance f12 = 2∙f(O) - f(H) is the primary form of generalized electron balance (GEB), completing the set of equations needed for quantitative description of electrolytic redox systems, f12 = pr-GEB.